Interrelations of adolescent’s identity development, differentiation of self and parenting style - Ragelienė, Tija; Justickis, Viktoras (Psichologija, 2016)
Relationship with parents and quality of this relationship take an essential role in the process of an adolescent’s identity development, yet the pathways linking parenting styles to adolescent’s identity development are not well understood. This study aims to investigate the interrelations between parenting styles, differentiation of self and adolescent identity development. In total, 804 adolescents took part in this study and filled the questionnaire. The age of participants ranges from 14 to 18 years old. The study explores whether the links from parenting style to adolescent’s identity diffusion operate through the differentiation of self. Results of a sequential mediation model revealed significant indirect effects of parenting style on adolescent’s identity diffusion operating through the differentiation of self for boys. Parenting style also had a direct effect on identity diffusion for girls. Implications of these findings for understanding the processes through which parenting styles determine adolescent’s identity development and gender differences of these relationships are discussed.